2017
DOI: 10.3892/ol.2017.5701
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 regulates the radiosensitivity of non-small cell lung cancer cells by targeting TXNRD1

Abstract: Radiation treatment remains one of the major modalities in the treatment of lung cancer. Although the majority of patients initially respond to treatment with radiation, resistance inevitably develops and leads to treatment failure. Therefore, the identification of the underlying molecular mechanisms of radiation resistance may facilitate the development of novel approaches for overcoming resistance, and enhance the efficacy of treatment with radiation in lung and other types of cancer. In the present study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…miR‐146b‐5p can inhibit NSCLC by targeting MMP16 and TRAF6 (Li, Zhang, et al, ). miR‐124 can regulate the radiosensitivity of NSCLC by targeting TXNRD1 (Hao et al, ). miR‐124 can suppress NSCLC progression by inhibiting CD164 signaling (Lin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…miR‐146b‐5p can inhibit NSCLC by targeting MMP16 and TRAF6 (Li, Zhang, et al, ). miR‐124 can regulate the radiosensitivity of NSCLC by targeting TXNRD1 (Hao et al, ). miR‐124 can suppress NSCLC progression by inhibiting CD164 signaling (Lin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are critical to cell growth, development, proliferation, differentiation, and death [17]. Growing evidence has demonstrated that miRNAs are involved in the regulation of tumor radiosensitivity [18][19][20][21][22][23][24][25][26][27]. It has previously been reported that miR-148b acts as a tumor suppressor in the context of lung cancer [28], cervical cancer [29], and gastric cancer [30].…”
Section: Ivyspringmentioning
confidence: 99%
“…TXNRD1 was widely reported to participate in the positive regulation of hepatocellular carcinoma [ 58 60 ]. In addition, TXNRD1 was observed to contribute to the development of lung cancer [ 61 ] and breast cancer [ 62 , 63 ]. However, researchers are yet to provide detailed explanations regarding the relationship between TXNRD1 and ESCC.…”
Section: Introductionmentioning
confidence: 99%